AN ENHANCEMENT OF GUIDANCE AND COUNSELING TEACHERSâ PROFICIENCY THROUGH TRAINING COUNSELING RATIONAL EMOTIVE BEHAVIOR - Asni, Asni; Marsinun, Rahmiwati (Jurnal Konselor, 2015)
The purpose of this research is to increase proficiency of guidance and counseling teachers by conducting training counseling of rational emotive behavior for the guidance and counseling teachers of Junior High Schools, Senior High Schools and Vocational Schools in Muhammadiyah Jakarta. The training method used was varied lecture, simulation and recitation by assigning the fieldwork to apply counseling rational emotive behavior (REB) in their schools. The results of this study revealed that the skill of counseling teachers increased up to 33,9 %. Moreover, the participants organized steps of counseling REB, starting from guidance relations, management of thought and views, management of emotion and affection and management of behavior stages.Keywords: Proficiency, Counseling Rasional Emotive Behavior